American culture in the 1910s - Whalan, Mark, 1974- (Twentieth-century American culture., 2010)
This book provides a fresh account of the major cultural and intellectual trends of the United States in the 1910s, a decade characterised by war, the flowering of modernism, the birth of Hollywood, and Progressive interpretations of culture and society. Chapters on fiction and poetry, art and photography, film and vaudeville, and music, theatre, and dance explore these developments, linking detailed commentary with focused case studies of influential texts and events. These range from Tarzan of the Apes to The Birth of a Nation, from the radical modernism of Gertrude Stein and the Provincetown.